2023
DOI: 10.1021/acs.jmedchem.2c01561
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Suite of Gadolinium-Free OATP1-Targeted Paramagnetic Probes for Liver MRI

Sean W. McRae,
Michael Cleary,
Daniel DeRoche
et al.

Abstract: Five amphiphilic, anionic Mn(II) complexes were synthesized as contrast agents targeted to organic anion transporting polypeptide transporters (OATP) for liver magnetic resonance imaging (MRI). The Mn(II) complexes are synthesized in three steps, each from the commercially available trans-1,2-diaminocyclohexane-N,N,N′,N′-tetraacetic acid (CDTA) chelator, with T 1-relaxivity of complexes ranging between 2.3 and 3.0 mM–1 s–1 in phosphate buffered saline at an applied field strength of 3.0 T. Pharmacokinetics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The prolonged contrast enhancement of Fe­(L2) observed in the kidneys over 4 h is reminiscent of cationic Fe­(III) macrocyclic complexes we have reported. , The prolonged enhancement of Fe­(L2) observed in the liver is even more remarkable and suggests that this complex clears largely through the hepatobiliary pathway. Contrast agents have been developed for imaging the liver, but these are generally anionic complexes that are amphiphilic due to an appended aromatic group, often an ethoxy-benzyl group . In contrast, Fe­(L2) is a cationic complex with two heterocyclic pendants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged contrast enhancement of Fe­(L2) observed in the kidneys over 4 h is reminiscent of cationic Fe­(III) macrocyclic complexes we have reported. , The prolonged enhancement of Fe­(L2) observed in the liver is even more remarkable and suggests that this complex clears largely through the hepatobiliary pathway. Contrast agents have been developed for imaging the liver, but these are generally anionic complexes that are amphiphilic due to an appended aromatic group, often an ethoxy-benzyl group . In contrast, Fe­(L2) is a cationic complex with two heterocyclic pendants.…”
Section: Resultsmentioning
confidence: 99%
“…Contrast agents have been developed for imaging the liver, but these are generally anionic complexes that are amphiphilic due to an appended aromatic group, often an ethoxy-benzyl group. 52 In contrast, Fe(L2) is a cationic complex with two heterocyclic pendants. Further studies are required to understand this pharmacokinetic clearance profile.…”
Section: Mri Studies In Micementioning
confidence: 99%
“…Due to their excellent T1 enhancement effect, gadolinium-based contrast agents (GBCAs) with linear or macrocyclic ligands have been the focus in both preclinical and clinical applications. , However, the extensive usage has revealed potential safety concerns with GBCAs. The leakage of gadolinium ions from the ligands has caused nephrogenic systemic fibrosis in patients with chronic kidney disease, and the subsequent discovery of gadolinium deposition in the brain and bones led to additional restrictions with strict regulation. , Despite the suspension of several linear GBCAs by the European Medicines Agency, Gd-EOB-DTPA and Gd-BOPTA with linear ligands continue to be used in clinics for hepatobiliary imaging . This makes it increasingly attractive to design novel macrocyclic GBCAs or to find gadolinium-free alternatives with hepatobiliary-specific imaging capabilities. , …”
Section: Introductionmentioning
confidence: 99%
“…and chelates (Mn-EDTA, Mn-CDTA, Mn-PyC3A, Mn-PC2A, etc.) (Chart S1) were introduced to design novel hepatobiliary contrast agents. ,, A recent study has shown in more detail that hepatic uptake and blood clearance are correlated with estimated octanol/water partition coefficients (est. log P ), which is used to quantify the lipophilicity of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although nanomaterials, such as MnO and MnO 2 , represent unique physicochemical properties like high relaxation rates and the possibility of diverse functionalizations, their drawbacks including harsh synthetic conditions, poor reproducibility, in vivo biodegradation difficulties, and ambiguous toxicity prevent the translation in the following clinical setting . Relatively speaking, small-molecule imaging probes featuring easy synthesis and modification, clear metabolism, and satisfactory repeatability are widely used in biomedical imaging. For example, Mn-PyC3A, which is a new type of extracellular fluid contrast agent invented by Caravan’s group, has recently entered phase 1 clinical trials (NCT05413668). Indeed, these small-molecule manganese-based contrast agents (MBCAs) reported so far manifest appropriate kinetic and relaxometric properties, but the ability to assess kidney dysfunction remains to be explored.…”
Section: Introductionmentioning
confidence: 99%